THEORETICAL ANALYSIS OF THE MANAGEMENT OF THE SYSTEM OF WORKING WITH YOUTH IN HIGHER EDUCATION - Aripova Ziyoda Atkhamovna (Western European Studies, 2024)
In this article we examine the theoretical frameworks that inform management of youth work in higher education. By exploring key theoretical perspectives and frameworks, we aim to provide insight into how institutions can effectively support the holistic development and well-being of young people in higher education.
Keywords: youth; education; training